Nutritional Factors Influencing Preterm Birth Risks and Fetal Development - Aziz un Nabi; Atta Ullah; Jaweria Gul; Umm-e-Kulsoom; Muhammad Siab; Abdullah (Research Journal of Psychology, 2025)
Background: Defined as delivery before 37 weeks of gestation, preterm birth (PB) still presents a serious worldwide health issue that greatly increases newborn morbidity and mortality. Objectives: To look at how preterm birth risks and fetal development might be affected by mother food choices, coffee intake and systematic impediments. Methods: Involving 400 women, a cross-sectional study was carried out in the Malakand area between March and July 2020. Data were gathered by means of standardized questionnaires sent to individuals and healthcare professionals. Important factors examined were mother caffeine intake, knowledge of dietary guidelines and socioeconomic constraints. Results: Of the participants, 33% suffered with PB; 75% of these women drank more than five cups of coffee daily, compared to 10.1% in full-term cases (p = 0.001). Of PB patients, 76.8% cut caffeine intake post-delivery; in contrast, 100% of high-caffeine consumers in full-term cases cut intake during pregnancy. Lack of awareness about nutrition (68%, p = 0.001). Conclusion: Preterm birth risks are greatly influenced by excessive caffeine use as well as by systematic obstacles including financial restrictions and lack of dietary support. Improving pregnancy results depends mostly on proactive dietary interventions, nutritional education and culturally responsive support networks.